2011
DOI: 10.19030/jabr.v22i1.1446
|View full text |Cite
|
Sign up to set email alerts
|

Are Tax Incentive Provisions Always Operative? Evidence From The Greek Manufacturing Industry

Abstract: <p class="MsoBodyText" style="text-align: justify; margin: 0in 34.2pt 0pt 0.5in; tab-stops: 387.0pt;"><span style="font-size: 10pt; font-weight: normal; mso-bidi-font-style: italic;"><span style="font-family: Times New Roman;">Tax incentives have been provided in many countries with the ultimate goal of making the cost of capital cheaper and thus enabling the development process through the increase of investment expenditures. The study of the role of tax incentives in investment spending has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Mainly the curb to liberalized tax laws came after 1973 and the marginal effective tax rates turned positive. As we have seen elsewhere (Anastassiou, 2006a) the application of investment allowances that were legislated for some of the years after 1973 could have caused, in combination with accelerated depreciation, a value of z larger than unity. But it was shown that these investment allowances were inoperative at the margin and then the final result, as can be seen from Table (1), Columns 1 and 3, was a positive marginal effective tax rate.…”
Section: Greek Marginal Effective Tax Rates and Total Averaged Ratesmentioning
confidence: 91%
“…Mainly the curb to liberalized tax laws came after 1973 and the marginal effective tax rates turned positive. As we have seen elsewhere (Anastassiou, 2006a) the application of investment allowances that were legislated for some of the years after 1973 could have caused, in combination with accelerated depreciation, a value of z larger than unity. But it was shown that these investment allowances were inoperative at the margin and then the final result, as can be seen from Table (1), Columns 1 and 3, was a positive marginal effective tax rate.…”
Section: Greek Marginal Effective Tax Rates and Total Averaged Ratesmentioning
confidence: 91%
“…Of course z refers to a present value of future deductions. But as has been found (Anastassiou, 2005), the amounts of investment expenditures undertaken during all these years were much higher than the amount of profits, and deductions on these investments for depreciation purposes were carried forward so in a specific year they were reducing (if not nullifying) substantially taxable profits. 8.…”
Section: Notesmentioning
confidence: 96%
“…In Table (1), using the depreciation rates for tax purposes 4 , and for Area A (Athens-Piraeus and surrounding areas comprising the Department of Attica), the corresponding values of z have been calculated for equipment and buildings. It was chosen to report on Area A, since it is believed (and there are a lot of indications to support this supposition) 5 that the representative firm is situated in the Attica Department.…”
Section: The Value Of Z In the Greek Manufacturing Industrymentioning
confidence: 99%
See 1 more Smart Citation